2023
DOI: 10.2147/idr.s418523
|View full text |Cite
|
Sign up to set email alerts
|

Hypervirulent Klebsiella pneumoniae

Abstract: Hypervirulent Klebsiella pneumoniae (hvKP), especially multidrug-resistant hvKP (MDR-hvKP) infections, are distributed globally, and lead to several outbreaks with high pathogenicity and mortality in immunocompetent individuals. This is usually characterized by a rapidly metastatic spread resulting in multiple pyogenic tissue abscesses. To date, even though the explanation of hypervirulent factors of hvKP has been identified, it still remains to be fully understood. The most common key virulence agents of hvKP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Our study also lacks information on the antimicrobial susceptibility profiles of the K. pneumoniae isolates. Hence, antibiogram data should be incorporated into hvKp surveillance studies in the future, as multidrug-resistant hvKp strains are increasingly being reported worldwide [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also lacks information on the antimicrobial susceptibility profiles of the K. pneumoniae isolates. Hence, antibiogram data should be incorporated into hvKp surveillance studies in the future, as multidrug-resistant hvKp strains are increasingly being reported worldwide [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…HvKp most commonly causes community-acquired infection in healthy individuals and is also associated with diabetes mellitus [ 48 , 49 , 50 , 51 ]. It typically causes cryptogenic, rapidly progressive, and metastatic abscess-forming disease, which is often fatal [ 52 ]. The remarkable ability of Klebsiella pneumoniae to share genetic information has led to the convergence of cKp and HvKp, leading to multi-drug resistant (MDR), hypervirulent strains [ 53 ] that pose an unmet, global health threat.…”
Section: Hypervirulent Klebsiella Pneumoniaementioning
confidence: 99%
“…To counter this, Klebsiella pneumoniae secretes four siderophores, which can efficiently sequester both free and bound iron. The siderophores aerobactin and salmochelin are highly expressed in HvKp compared to cKp [ 52 ] and are associated with hypermucoid capsule production [ 61 ]. A high total siderophore concentration is also strongly predictive of HvKp [ 62 ].…”
Section: Hypervirulent Klebsiella Pneumoniaementioning
confidence: 99%
“…Though hvKp has been studied for nearly 40 years, its definition remains unclear and controversial ( Chen et al, 2023 ). Many studies summarized the differences between hvKp and CKP, clinical manifestations, capsule typing, hypermucoviscosity, and virulence genes are helpful to identify hvKp ( Choby et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%